2016
DOI: 10.3390/ma9080698
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Property of Open-Hole Steel Plates Influenced by Bolted Clamp-up and Hole Fabrication Methods

Abstract: Steel plates with open holes are commonly used in structural assemblies. The fatigue properties of such details are influenced by bolted clamp-up and hole fabrication methods. The fracture surface, stiffness degradation and fatigue life of test specimens are investigated in detail and compared with the contemporary test data. The analysis results show that the presence of draglines greatly influences the fatigue crack initiation at the open-hole cut by laser. The bolted clamp-up condition greatly enhances the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Thermo‐expandable microspheres (EMs) are composed of thermoplastic polymer shells and liquid alkanes encapsulated in them 34 . Generally, the diameter of EMs is 10–30 μm, and the thickness of the polymer shell is 2–15 μm 35 . Due to the excellent elasticity of the polymer shell, when the microsphere is heated, with the gasification and expansion of internal alkanes, the volume of the microsphere increases several times without damage to the core−shell structure 36 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermo‐expandable microspheres (EMs) are composed of thermoplastic polymer shells and liquid alkanes encapsulated in them 34 . Generally, the diameter of EMs is 10–30 μm, and the thickness of the polymer shell is 2–15 μm 35 . Due to the excellent elasticity of the polymer shell, when the microsphere is heated, with the gasification and expansion of internal alkanes, the volume of the microsphere increases several times without damage to the core−shell structure 36 .…”
Section: Introductionmentioning
confidence: 99%
“…34 Generally, the diameter of EMs is 10-30 μm, and the thickness of the polymer shell is 2-15 μm. 35 Due to the excellent elasticity of the polymer shell, when the microsphere is heated, with the gasification and expansion of internal alkanes, the volume of the microsphere increases several times without damage to the core−shell structure. 36 Therefore, such EMs can be used as a physical foaming agent to prepare foam materials with perfect closed cell structure.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that crack growth in the open-hole specimens initiated almost exclusively at the edge of the hole. Thru thickness crack development around the edge of the hole appeared to be unsymmetrical in most cases [11]. The fatigue life of riveted sheet metal joints consisting of single as well as specimens with multiple fasteners was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the authors have also conducted a series of fatigue experimental research and comprehensive review of research work can be referred to [ 1 , 2 , 24 ]. For the improvement of fatigue strength, some other techniques, such as bolt clamp-up and carbon fibre-reinforced polymer (CFRP) strengthening, have also been recently highlighted by the authors [ 24 ] and other researchers. In [ 24 ], the combination of bolt clamp-up action was considered in the improvement of fatigue strength.…”
Section: Introductionmentioning
confidence: 99%
“…For the improvement of fatigue strength, some other techniques, such as bolt clamp-up and carbon fibre-reinforced polymer (CFRP) strengthening, have also been recently highlighted by the authors [ 24 ] and other researchers. In [ 24 ], the combination of bolt clamp-up action was considered in the improvement of fatigue strength. For the test specimen with centre hole covered with CFRP as reported in [ 25 ], it was shown an increased fatigue life of 54% over the un-retrofitted ones, while that only applied on either side of the crack starter exhibited only 25% life enhancement.…”
Section: Introductionmentioning
confidence: 99%